Hyper Biblical : antidote for modern day false teaching - Jeyaraj, Duke (Chennai, India. Notion Press, 2024)
We must do more! We must 'contend for the faith once for all delivered for the saints'. We must open our mouths and uncork our pens to warn about 'savage wolves which will come among you (the local church believers) not sparing the flock'. Spread virally, thanks to the social media, modern cultic false teachings such as (1) Hyper-Grace ('No judgement for believers post-Cross'), (2) Hyper-Supernaturalism ('It is always God's will to heal me here and now', 'Believers in Jesus need not die, if they chose to'), and (3) Hyper-Love ('Everyone is already saved, but they just don't know it yet!', 'You will stop existing in hell or will eventually come to heaven from there') have locust-swarmed churches in South Indian cities and beyond. In this book, the incensed author, argues vehemently from the Bible to show how much these scripture-twisting, half-truth-full-of, diabolical teachings have majorly deviated from the 'whole counsel of God'. The author offers these 'five loaves and two fish' unto the Lord! Perhaps, the Lord use it for the restoration of the gangrene-of-false-teaching infested Body of Christ, back to sound doctrinal health (this book also includes a section where there is an antidote against false teaching). Those embracing these false teachings must be warned to steer clear of this book as it would greatly infuriate them, calling a spade, a spade, without 'putting blade' (using illustrations from the world of Cricket)! The author's prayer is that the Holy Spirit could possibly cajole and convince such blood-bought, precious, believers, through these peppery pages, to swiftly abandon these eternity-shipwrecking doctrines and wholly embrace biblical, balanced, sound doctrine!
Keywords: Christian Theology; False Teaching.-- Christianity; Bible and False teaching; Religion.-- Theology; Theology.-- Doctrinal; Hyper-Grace